Do fracionamento decisório: fato e sua resolubilidade parcial como requisitos da cisão da decisão judicial. - Lemos, Vinicius Silva (2019)
The present work has the purpose to analyze the possibility of the cognitive split and the decisionary fractionation in the common process, considering the positivity brought from the Code of Civil procedure from 2015, upon the insertion of the articles 354 paragraph 356. The focus of this research is the constructive concepcion of the necessary requirements so the decisionary fractionation can be possible, which the criterias for possibility upon a complex process, either by the plurality of requests or the plurality of parts, culminating in a group of juridical relations that must be solved on the decision. Even though the cognitive split is not something new in the procedural ordering, it is new how open and positive the clause is in the common procedure, which before was delegated to the speciality of the specific procedures for the possibilitation of the cognitive split and the decisory fractionation. The possibility of a procedure be split into this decision making aspect needs a diversity of requirements, which are delimited as the problem of the present work, in order to build a relationship between the objective complexity of the demand and the existence of the plurality of questions, in fact, in it’s partial solvability and the maintenance of issues that can only be solved after a specific probative instruction. For the present research, the methodology adopted is the deductive, through a literature review on the subject, in an overview of the institutes related to the theme, like a contentious object of the procedure, cause of claim, request, compilation of requests, judicial decision, chapters of the sentence, judicial cognition and demand merits of the claim, in order to deductively construct a specific result about the proposed problem. After studying those institutes and reviewing the literature, the construction of the problem’s answer emerges through analysis over the formative aspects of the procedure objectively complex, the development toward the uniqueness of the sentence as a rule and the positive possibility to the decisory fractionation through a cognitive split. There is still a constructive analysis of the possibility of fulfilling the requirements for a decisive relationship, the inviability in some situations, the material hypotheses and the way the decision is constructed, it can be with or without merit, through the parts attitudes - the plaintiff and the defendant - and the judgment in a necessary cognitive perception about the existence of cognitive bifurcation demand. It is important to show that the confrontation about the appeal challenge of a non fulfillment of the requirements for the decisory fractionation and the impact of an eventual appeal, as well as the judgmental partial and the consequences of the proper decision and the rest of the demand that has lis pendens. The conclusion shows that the existence of the necessary requirements for this cognitive split and the decisory fractionation, with a necessary relation to the plurality of questions of fact, partial resolvability in the face of objectively complex judicial protection.